2016
DOI: 10.1016/j.scitotenv.2016.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of inorganic arsenic exposure and cancer risk via consumption of vegetables in southern selected districts of Pakistan

Abstract: Human exposures to arsenic (As) through different pathways (dietary and non-dietary) are considered to be one of the primary worldwide environmental health risks to humans. This study was conducted to investigate the presence of As in soil and vegetable samples collected from agricultural lands located in selected southern districts of Khyber Pakhtunkhwa (KPK) Province, Pakistan. We examined the concentrations of total arsenic (TAs), organic species of As such as monomethylarsonic acid (MMA) and dimethylarsoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 99 publications
(96 reference statements)
3
29
2
1
Order By: Relevance
“…Available data for the association between vegetable consumption and As exposure are limited. A Pakistan study reported that iAs exposure from vegetable consumption is not a major cancer risk factor [75]. While our data showed that some vegetable food items (leafy vegetables, mashed vegetables, and fried vegetables) are positively associated with toenail As, the association is likely attributable to the high water As content of the vegetable items or their preparation method.…”
Section: Discussioncontrasting
confidence: 62%
“…Available data for the association between vegetable consumption and As exposure are limited. A Pakistan study reported that iAs exposure from vegetable consumption is not a major cancer risk factor [75]. While our data showed that some vegetable food items (leafy vegetables, mashed vegetables, and fried vegetables) are positively associated with toenail As, the association is likely attributable to the high water As content of the vegetable items or their preparation method.…”
Section: Discussioncontrasting
confidence: 62%
“…The total land under cultivation is approximately 5225.71 km 2 , with planted with various vegetables and other food crops (Rehman et al, 2016; Waqas et al, 2014). Wheat, barley, maize, rice, sugarcane, cucumber, bitter melon, ridge gourd, onion, garlic, mint, lady finger, squash-melon, lettuce, spinach, pea, pumpkin, cabbage, cauliflower, potato, bringal, turnips, pepper, carrot, radish, tomato, yam, perslane, Chinese onion, and coriander are the most important food-crops grown in the study area.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…After air drying, the soil samples were mechanically ground and passed through a sieve of 2-mm mesh, and preserved in clean zip sealed plastic bags for further chemical analyses. Basic soil properties such as pH, electrical conductivity, total carbon, nitrogen and sulfur, dissolved organic carbon (DOC), soil texture, and bulk density are presented in our previous studies (Waqas et al, 2014; Rehman et al, 2016). …”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…Arsenic (As) is one of the toxic metalloids and can cause toxicological effects on all living organisms (Rosas-Castor, Guzmán-Mar, Hernández-Ramírez, Garza-González, & Hinojosa-Reyes, 2014;Tripathi, Singh, Mishra, Tripathi, & Nautiyal, 2015;Vázquez et al, 2015). Soil contamination with heavy metal(oid)s due to anthropogenic activities, such as industrial activities, agrochemical application, and mining (Rehman et al, 2016), results in land degradation (Khaledian, Kiani, Ebrahimi, Brevik, & Aitkenhead-Peterson, 2016;Roy & McDonald, 2015). Natural processes are major causes of As contamination in land (Liu et al, 2010;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%